Pelatihan Pembuatan Media Pembelajaran Aplikasi Android Berbasis Smart APPS Creator untuk Meningkatkan Kemampuan Inovasi Guru Pendidikan Agama Islam - Aeni, Ani Nur; Djuanda, Dadan; Rukmana, Kusman; Maulana, Marwan; Akbar, Kamal Aramdan; Hafidz, Achmad Nurul; Al-Faridzi, Muhammad Dzikri Ajri (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
The ability of teachers to make digital learning tools is one of the competencies that must be mastered, namely pedagogic competence and professional competence. Elementary Islamic Religious Education teachers must be able to create innovative learning media as a necessity for teaching in this digital era. Improving teachers' innovation abilities can be done independently or officially through training. The training on making SAC learning media is one of the efforts to increase teacher innovation. This training was attended by 44 participants consisting of elementary Islamic Religious Education teachers in Sumedang. The training lasted for 32 hours of learning which was carried out in offline and online mode. Through this training, the results of elementary school Islamic Religious Education teachers were obtained: 1) able to improve their innovation ability in making learning media armed with training materials about Applications as learning media and application design materials, 2) able to use SAC to make android application learning media armed with instructions from instructors during online meetings, training modules volumes 1-7 and video tutorials for making SAC-based android applications. Through this training, it can be recommended to teachers to improve the ability to innovate in learning, one of which is by mastering SAC as an application to create android application learning media.